Knowledge exchange roles and EKR performance impact: extending the theory of knowledge reuse. Issue 1 (2nd January 2018) - Forsgren, Nicole; Sabherwal, Rajiv; Durcikova, Alexandra
Abstract: Organisations are spending considerable resources on electronic knowledge repositories (EKRs) that should have a positive effect on employees' EKR performance impact. Seeking to build on and extend the theory of knowledge reuse, this paper focuses on the various roles individuals play in knowledge exchange, and how the knowledge exchange role mediates the effect of previously studied individual perceptual variables (perceived time pressure, extrinsic and intrinsic rewards, and knowledge contribution self-efficacy) on EKR performance impact. In order to identify the various knowledge exchange roles, we simultaneously consider both knowledge contribution process (embedded vs. separate activity) and knowledge reuse (internal EKR, external EKR, colleagues, manuals, knowledge self-reliance). When work is highly specialised and technical as in the context of system administrators, we observed four roles: Self-reliant Contributors, Detached Moderates, Involved Brokers, and Reluctant Limited Users. Results indicate that the effects of intrinsic rewards and knowledge contribution self-efficacy on EKR performance impact are fully mediated by knowledge exchange role. Perceived time pressure does not influence either knowledge exchange roles or EKR performance impact. Overall, the paper provides insights into roles individuals play in knowledge exchange, and extends the theory of knowledge reuse.